2021
DOI: 10.1002/jaba.892
|View full text |Cite
|
Sign up to set email alerts
|

On the generality of preference for contingent reinforcement

Abstract: Reinforcers can be delivered dependent on or independent of responding. Both human and nonhuman animals have shown a preference for contexts involving contingent reinforcement, but the generality of this phenomenon to humans and its implications have not yet been described. We present an integrative summary of studies evaluating preference for contingent versus noncontingent reinforcement, including (a) study participants, reinforcer types, response topographies, and contexts; (b) outcomes; (c) potential varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 39 publications
0
7
1
Order By: Relevance
“…First, the GBG provides students an opportunity to earn a reward that is otherwise not available in their classroom. Second, the GBG provides clear rules and consequences for following and not following the rules and students may prefer consistency in the correspondence between the rules and the consequences (Gover et al, 2022). Third, the corrective feedback provided during the GBG is helpful in that it is tied to reward delivery, unlike corrective feedback during baseline.…”
Section: Discussionmentioning
confidence: 99%
“…First, the GBG provides students an opportunity to earn a reward that is otherwise not available in their classroom. Second, the GBG provides clear rules and consequences for following and not following the rules and students may prefer consistency in the correspondence between the rules and the consequences (Gover et al, 2022). Third, the corrective feedback provided during the GBG is helpful in that it is tied to reward delivery, unlike corrective feedback during baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Research has repeatedly shown that humans tend to prefer contingent over noncontingent reinforcement schedules (Gover et al, 2022 ; Luczynski & Hanley, 2009 ). Presumably, this is because contingent schedules allow for reinforcement delivery when the relevant motivating operations are in place, therefore maximizing the value of the reinforcers.…”
Section: Applied Implicationsmentioning
confidence: 99%
“…Such investigations are necessary to confirm schedule-induced responding as important for the attachment patterns in infancy (Beckes et al, 2017). Similarly, exploring the impact of VR schedules on verbal behavior development is also a promising area for future research (Gover et al, 2021; Hanratty & Hanley, 2021; Luczynski et al, 2014).…”
Section: Future Directionsmentioning
confidence: 99%
“…However, for examples of the utilization of VR for facilitating functional communication skills, see the work of Hanley and colleagues (e.g.,Gover et al, 2021;Hanratty & Hanley, 2021;Luczynski et al, 2014).…”
mentioning
confidence: 99%